KEBIJAKAN PENGELOLAAN LIMBAH MEDIS PASCA COVID-19 DI INDONESIA DAN IMPLIKASINYA TERHADAP EKOSISTEM LAUT - Asbullah, Andi Anggun Ainul Khaliq; Darwis; Supriadi, Imam Fadhil Nugraha (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
This research analyzes the implementation of medical waste management policies in Indonesia, focusing on the challenges of infrastructure, public awareness, and law enforcement. In addition, it explores the impacts of poorly managed medical waste on marine ecosystems, which include threats to marine life, disruption to the food chain, and health risks to humans. The results showed that medical waste management in Indonesia still faces significant obstacles, mainly related to the lack of public awareness on the importance of sustainable medical waste management. The lack of public understanding of the long-term impact of medical waste containing hazardous chemicals and microplastics results in improper waste disposal practices. Waste such as masks, gloves, and other medical equipment often end up in the ocean, disrupting the ecosystem and threatening of sustainability pf the food chain. The results of this study emphasize the importance of increasing public awareness and enforcing stricter regulations in maintaining the health of the marine environment and ecosystem.